Facts about Wildlife Diseases: Pseudorabies - Samantha Wisely (EDIS, 2014)
Pseudorabies primarily affects swine, but cattle, sheep and other mammals are susceptible to infection. Humans are not at risk. The superficial symptoms of this viral disease resemble rabies symptoms, thus the name pseudorabies. Although eliminated in commercial animals, feral swine populations in the United States continue to circulate the disease and provide a reservoir for outbreaks. Texas, Oklahoma, Florida, and Hawaii all have dense populations of feral swine with a high prevalence of pseudorabies. Feral swine, therefore, pose a serious risk to commercial swine operations, livestock, companion animals, and wildlife. This 4-page fact sheet was written by Samantha Wisely and published by the UF Department of Wildlife Ecology and Conservation, August 2014.